Math Problems

MathematicsArithmeticFractions → Adding Fractions

Get a common denominator in order to evaluate the following

Questions

 $$\frac{1}{5} - \frac{1}{9} =$$ _______ $$\frac{2}{5} - \frac{1}{9} =$$ _______ $$\frac{3}{5} - \frac{1}{2} =$$ _______ $$\frac{7}{8} + \frac{1}{8} =$$ _______ $$\frac{6}{7} + \frac{5}{7} =$$ _______ $$\frac{1}{2} - \frac{7}{8} =$$ _______ $$\frac{4}{5} - \frac{4}{5} =$$ _______ $$\frac{1}{3} + \frac{5}{9} =$$ _______ $$\frac{1}{3} + \frac{1}{4} =$$ _______ $$\frac{2}{7} - \frac{1}{9} =$$ _______ $$\frac{1}{7} + \frac{5}{8} =$$ _______ $$\frac{1}{2} - \frac{1}{8} =$$ _______ $$\frac{1}{2} + \frac{4}{7} =$$ _______ $$\frac{3}{5} + \frac{1}{2} =$$ _______ $$\frac{5}{6} - \frac{5}{8} =$$ _______ $$\frac{2}{7} + \frac{7}{9} =$$ _______ $$\frac{2}{9} - \frac{7}{9} =$$ _______ $$\frac{3}{5} + \frac{1}{3} =$$ _______ $$\frac{1}{3} + \frac{8}{9} =$$ _______ $$\frac{2}{3} - \frac{2}{3} =$$ _______ $$\frac{2}{3} + \frac{4}{9} =$$ _______ $$\frac{1}{4} - \frac{1}{2} =$$ _______ $$\frac{2}{9} - \frac{1}{3} =$$ _______ $$\frac{4}{5} + \frac{3}{5} =$$ _______ $$\frac{3}{4} + \frac{7}{9} =$$ _______ $$\frac{4}{5} + \frac{7}{8} =$$ _______ $$\frac{8}{9} + \frac{8}{9} =$$ _______ $$\frac{2}{5} + \frac{8}{9} =$$ _______

 $$\frac{1}{5} - \frac{1}{9} = \frac{4}{45}$$ $$\frac{2}{5} - \frac{1}{9} = \frac{13}{45}$$ $$\frac{3}{5} - \frac{1}{2} = \frac{1}{10}$$ $$\frac{7}{8} + \frac{1}{8} = 1$$ $$\frac{6}{7} + \frac{5}{7} = 1 \frac{4}{7}$$ $$\frac{1}{2} - \frac{7}{8} = \frac{-3}{8}$$ $$\frac{4}{5} - \frac{4}{5} = \frac{0}{1}$$ $$\frac{1}{3} + \frac{5}{9} = \frac{8}{9}$$ $$\frac{1}{3} + \frac{1}{4} = \frac{7}{12}$$ $$\frac{2}{7} - \frac{1}{9} = \frac{11}{63}$$ $$\frac{1}{7} + \frac{5}{8} = \frac{43}{56}$$ $$\frac{1}{2} - \frac{1}{8} = \frac{3}{8}$$ $$\frac{1}{2} + \frac{4}{7} = \frac{15}{14}$$ $$\frac{3}{5} + \frac{1}{2} = 1 \frac{1}{10}$$ $$\frac{5}{6} - \frac{5}{8} = \frac{5}{24}$$ $$\frac{2}{7} + \frac{7}{9} = \frac{67}{63}$$ $$\frac{2}{9} - \frac{7}{9} = \frac{-5}{9}$$ $$\frac{3}{5} + \frac{1}{3} = \frac{14}{15}$$ $$\frac{1}{3} + \frac{8}{9} = 1 \frac{2}{9}$$ $$\frac{2}{3} - \frac{2}{3} = \frac{0}{1}$$ $$\frac{2}{3} + \frac{4}{9} = 1 \frac{1}{9}$$ $$\frac{1}{4} - \frac{1}{2} = \frac{-1}{4}$$ $$\frac{2}{9} - \frac{1}{3} = \frac{-1}{9}$$ $$\frac{4}{5} + \frac{3}{5} = \frac{7}{5}$$ $$\frac{3}{4} + \frac{7}{9} = 1 \frac{19}{36}$$ $$\frac{4}{5} + \frac{7}{8} = 1 \frac{27}{40}$$ $$\frac{8}{9} + \frac{8}{9} = 1 \frac{7}{9}$$ $$\frac{2}{5} + \frac{8}{9} = 1 \frac{13}{45}$$